Case Report: Wound Closure Acceleration in a Patient With Toxic Epidermal Necrolysis Using a Lyophilised Amniotic Membrane - Lipový, Bretislav; Hladík, Martin; Štourač, Petr; Forostyak, Serhiy (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Toxic epidermal necrolysis (TEN) is a rare life-threatening disease that mainly affects the skin and mucous membranes, resulting from a toxic delayed-type hypersensitivity reaction type IV. The clinical symptoms are caused massive apoptosis of keratinocytes in the dermo-epidermal junction resulting in the formation of a bulla and subsequent separation of the entire epidermis with the exposure of dermis. The current local therapy of TEN involves the use of biological dressings for wound healing and helping acceleration of the skin wound closure (re-epithelialization), reduction the risk of complications development (infections) and pathological scar formation. This work presents a case study using a lyophilized amniotic membrane for accelerating wound healing in a patient with TEN. Case presentation: We report a case of an 8-year-old girl transferred to the centre with a histologically confirmed diagnosis of TEN. Despite the application of immunosuppressive therapy consisting of corticosteroids and intravenous immunoglobulins, we have observed disease progression and exfoliation of up to 60% of the total body surface area (TBSA). In the facial area, which is cosmetically privileged, we decided to use the lyophilized amniotic membrane (Amnioderm®) to cover up approximately 2% of the TBSA. Within two days after the application, we observed accelerated reepithelialisation, with rapid wound closure. We have not observed any side effects nor infections during the subsequent phases of wound healing. Skin defects in non-facial areas of the body were treated with synthetic dressings. When compared to the areas covered with the lyophilized AM, the healing process was prolonged. Conclusions: This is the first case study using a lyophilized amniotic membrane in the treatment of a patient with TEN. The AM application in the cosmetically-privileged area (face), proved to be very efficient in the treatment of TEN patients. The use of this allogeneic material demonstrated excellent biocompatibility and caused a unique acceleration of epithelialization and wound healing, yielding also excellent long-term results. The current study opens broad possibilities for clinical application of the used material, the improvement of current therapy of patients with TEN and better outcomes and recovery of patients.